The Influence Of E-Wallet Usage And Financial Literacy On Personal Financial Behavior Among Accounting Students Of The Faculty Of Economics And Business Tadulako University - Yusriyani, Yusriyani Herawaty Kurnia; Mile, Yuldi; Kahar, Abdul; Masdar, Rahma; Furqan, Andi Chairil (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The purpose of this study is to analyze the financial literacy of accounting students at the Faculty of Economics and Business, Tadulako University and how they use e-wallets. This study uses quantitative techniques to synthesize the results of experiments that test the influence of financial literacy and digital wallet use on personal financial behavior (variable Y). We used a sample size of 90 people for this study. Simple random sampling was used in this study for sampling purposes. The essence of simple random sampling is to randomly select a subset of the population from a larger population without considering demographic factors. Each research instrument has been proven to be valid and reliable based on the results of the research. Financial literacy and the use of digital wallets have a positive and significant impact on students' personal financial behavior. Research also shows that financial literacy has a great influence, suggesting that digital wallets and a strong understanding of money can shape students' spending habits to be more responsible and focused.